Associations between sport and screen-entertainment with mental health problems in 5-year-old children - Dezateux Carol; Dowda Marsha; Griffiths Lucy J; Pate Russell (BMC, 2010)
Abstract Background Few studies have examined the benefits of regular physical activity, and risks of sedentary behaviour, in young children. This study investigated associations between participation in sports and screen-entertainment (as components of physical activity and sedentary behaviour), and emotional and behavioural problems in this population. Methods Cross-sectional analysis of data from 13470 children (50.9% boys) participating in the nationally representative UK Millennium Cohort Study. Time spent participating in sports clubs outside of school, and using screen-entertainment, was reported by the child's mother at child age 5 years, when mental health was also measured using the Strengths and Difficulties Questionnaire. Results 45% of children did not participate in sport clubs and 61% used screen-entertainment for ≥ 2 hours per day. Children who participated in sport had fewer total difficulties; emotional, conduct, hyperactivity-inattention and peer relationship problems; and more prosocial behaviours. These relationships were similar in boys and girls. Boys and girls who used screen-entertainment for any duration, and participated in sport, had fewer emotional and behavioural problems, and more prosocial behaviours, than children who used screen-entertainment for ≥ 2 hours per day and did not participate in sport. Conclusions Longer durations of screen-entertainment usage are not associated with mental health problems in young children. However, our findings suggest an association between sport and better mental health. Further research based on longitudinal data is required to examine causal pathways in these associations and to determine the potential role of this and other forms of physical activity in preventing mental health disorders.